A challenging case of hypercapnic respiratory failure during pregnancy. (June 2021) - Vijayakumar, B; Cao, M; Mackillop, L; Sarangmat, N; Leite, MI; Wathen, CG; Nickol, AH; Turnbull, CD
We describe a 40-year-old female who presented with progressive breathlessness and hypercapnic respiratory failure during pregnancy secondary to undiagnosed muscle-specific kinase myasthenia gravis. Her presentation was progressive and protracted, having over five contacts with healthcare professionals over nine months, many of these predating her pregnancy. Her atypical presentation for myasthenia with minimal limb weakness led to consideration of other causes of hypercapnic respiratory failure. Once diagnosed, she was treated with intravenous immunoglobulin and non-invasive ventilation. She gave birth to a pre-term infant by planned caesarean section. Her insidious presentation and the progressive nature of her breathlessness were unusual and our report highlights the predominant involvement of respiratory muscles in muscle-specific kinase myasthenia. Her pregnancy may have further delayed her diagnosis due the attribution of some symptoms to normal pregnancy. Early recognition and treatment of myasthenia gravis are important to prevent life-threatening complications.